MANAJEMEN KELAS BERBASIS MULTIPLE INTELLIGENCE DALAM PENGEMBANGAN BAKAT (Studi Kasus MI Pembangunan UIN Jakarta ) - Harahap, Rahmad (Universitas Islam Negeri Sumatera Utara Medan, 2024)
The aim of this research is to describe multiple intelligence-based classroom management in the learning process, as well as to analyze its impact on student learning achievement and the development of student potential at MI Pembangunan UIN Jakarta. Based on these objectives, this research uses qualitative research with a descriptive approach. Data collection was carried out by conducting observations, interviews and documentation studies. Data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions by reviewing the data and theories that have been built in the research. The findings of multiple intelligence-based classroom management research at MI Pembangunan UIN Jakarta can be identified through three main aspects: 1) Multiple Intelligence Research, identifying students' main or dominant intelligence in various aspects of intelligence. The MIR test results show the diversity of students' intelligence. 2) Class management based on multiple intelligence. The method for grouping students is based on the same dominant type of intelligence, creating a conducive learning climate, and classroom facilities and equipment to create a learning environment that is effective, comfortable and supports the achievement of goals. 3) Class management based on multiple intelligence in the learning process. The implementation of a multiple intelligence-based classroom management approach at MI Pembangunan develops student potential through various coaching programs and lesson plans. 4) Multiple intelligence-based classroom management in developing student talents. Talent development at MI Pembangunan UIN Jakarta through the implementation of multiple intelligence-based classroom management with three key aspects: class division based on MIR results, creating a conducive learning climate, and providing supportive classroom facilities and equipment